2019
DOI: 10.3847/1538-4357/ab4793
|View full text |Cite
|
Sign up to set email alerts
|

Finding the Critical Decay Index in Solar Prominence Eruptions

Abstract: The background field is assumed to play prime role in the erupting structures like prominences. In the flux rope models, the critical decay index (n c ) is a measure of the rate at which background field intensity decreases with height over the flux rope or erupting structure. In the real observations, the critical height of the background field is unknown, so a typical value of n c = 1.5 is adopted from the numerical studies. In this study, we determined the n c of 10 prominence eruptions (PEs). The prominenc… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
(63 reference statements)
0
7
0
Order By: Relevance
“…(2019). Low values of the decay index at the height from which prominences start eruption were reported by Lee et al (2016), Vasantharaju et al (2019), Rees-Crockford et al (2020), Filippov (2020.…”
Section: Discussionmentioning
confidence: 69%
“…(2019). Low values of the decay index at the height from which prominences start eruption were reported by Lee et al (2016), Vasantharaju et al (2019), Rees-Crockford et al (2020), Filippov (2020.…”
Section: Discussionmentioning
confidence: 69%
“…In a data-driven MHD simulation, Guo et al (2019a) computed the decay index along the eruption path of a flux rope, and found that the rope starts to rise rapidly at the same height as the decay index crosses the canonical critical value of 1.5. Similarly, recent studies on the height-time profiles of eruptive filaments (Vasantharaju et al 2019;Zou et al 2019b;Myshyakov & Tsvetkov 2020;Cheng et al 2020) and of hot channels (Cheng et al 2020) generally concluded that the decay index at the height where the slow rise transitions to fast rise is close to the threshold of the torus instability.…”
Section: Torus Instabilitymentioning
confidence: 83%
“…But the ini-tial rise of prominence seems to be caused by coronal rain, which presumably is the result of thermal instability. Vasantharaju et al (2019) suggested that the slow rise phase can be connected with the ideal kink instability of flux rope. Let us examine this possibility for the event of May 16-18, 2011.…”
Section: Possible Mechanisms For the Initial Rise Of Prominencementioning
confidence: 99%
“…Most acceptable triggering mechanism for the prominence instability is connected to twisted magnetic config-urations. It has been observed that the kink instability of magnetic flux ropes (Williams et al 2005), the torus instability (Filippov 2013, Zuccarello et al 2014 or both together (Vasantharaju et al 2019) can lead to CME initiations.…”
Section: Introductionmentioning
confidence: 99%